National Primary Care Policy (2017) and the roles of community health workers - Juliana Roza Dias; Sonia Acioli; Vanessa de Almeida Ferreira Corrêa; Inês Leoneza de Souza; Ricardo de Mattos Russo Rafael; Paulo Henrique de Almeida Rodrigues; Glaucia Bohusch (Revista Brasileira de Enfermagem)
ABSTRACT Objective: To analyze the new roles of community health workers as outlined in the 2017 National Primary Care Policy (PNAB) from the perspectives of both nurses and community health workers. Methods: This qualitative study involved nurses and community health workers from Family Health teams, conducted through semi-structured interviews via videoconference between August 2021 and April 2022. The data were analyzed using thematic content analysis. Results: We identified professionals who argued that the new roles for community health workers aim to increase their autonomy and professional recognition. Others highlighted concerns about the loss of originality in their work and the potential for the illegal practice of nursing or nursing technician duties. Final Considerations: The 2017 PNAB emphasizes task execution for these workers, contributing to the mechanization of activities, reinforcing the biomedical model, and undermining the role of community health workers in promoting health within Primary Care.